Oblicza Boga w chrześcijaństwie starożytnym (XLIX Spotkanie Badaczy Antyku Chrześcijańskiego, Papieski Instytut Patrystyczny Augustinianum, Rzym, 11-13.05.2023) - Wysocki, Marcin (Vox Patrum, 2023)
Report from the XLIX Meeting of Scholars of Christian Antiquity, entitled "The Faces of God in Ancient Christianity", which took place at the Pontifical Patristic Institute Augustinianum, Rome, on May 11-13, 2023.